Correlación entre afrontamiento y autoestima en personas con VIH de la región de los ríos, Tabasco México - Maldonado, Lesli Tairi Anguiano; Poot, Rogelio Uribe; Contreras, Diana Cristell Pérez; Miranda de la Cruz, Armando; Gómez, Sergio Quiroz (European Scientific Journal, ESJ, 2017)
Introduction: the HIV is a disease that causes important complications of health; to achieve a good confrontation and to support a levelled autoesteem are fundamental factors for his treatment. Objective: to identify the relation between the autoesteem and the confrontation in the persons with HIV of the region of Tabasco’s rivers. Methodology: quantitative, descriptive study, correlacional of transverse court, n=64 participants. To measure the confrontation there was in use The Scale of Strategies modified of Coping; for the autoesteem there was in use the Scale of modified Cooper Smith. Results: 48.4 % belongs to the item of confrontation superior to the average; whereas 37.5 % presents discharge he autoestimates. The counterfoil of correlation showed a negative significant relation of the confrontation with the autoesteem rs =-.287. Conclusions: the age and the years of diagnosis are determinant for the autoesteem and the confrontation; the autoesteem and the confrontation are important for the treatment and recovery of the person with HIV / AIDS.